The short story of the miraculous daily resurrection of life in us - Vukoman Jokanović (Zaštita Materijala)
The development of modern science in various fields today often exceeds the limits and ideas of the bravest philosophers and scientists of our time. And certainly the most intriguing areas of research are those based on the molecular basis of life processes. The complexity and complexity of the human body, countless intertwined feedback loops that regulate internal processes in the body and enable its survival, can best be interpreted at the micro and nano level, ie at the level of the cell and its subcellular structures. This opens up huge potentials for understanding and influencing living systems, but also unlimited challenges for science. The monograph "How cells live and die in us" is unique in many ways. The multidisciplinary procedure provides a comprehensive overview of the complexity of the human body, as well as its possible functioning at the cellular micro and nano level, ie at the level of molecules, atoms, nuclei, protons, etc. The story is inspired by Balasevic's line between the year of birth and the year of death.